Principles of modeling and simulation : a multidisciplinary approach. - Sokolowski, John A., ....-; Banks, Catherine M., ....- (Hoboken : Wiley, 2009)
Table of Contents Pt. 1 Principles of Modeling and Simulation: A Multidisciplinary Approach 1 What Is Modeling and Simulation? 2 The Role of Modeling and Simulation Pt. 2 Theoretical Underpinnings 3 Simulation: Models That Vary over Time 4 Queue Modeling and Simulation 5 Human Interaction with Simulations 6 Verification and Validation Pt. 3 Practical Domains 7 Uses of Simulation 8 Modeling and Simulation: Real-World Examples 9 The Future of Simulation Index